Towards Engineering an Orthogonal Protein Translation Initiation System - Lee, Byeong Sung; Choi, Woon Jong; Lee, Sang Woo; Ko, Byoung Joon; Yoo, Tae Hyeon (Frontiers in Chemistry, 2021)
In the last two decades, methods to incorporate non-canonical amino acids (ncAAs) into specific positions of a protein have advanced significantly; these methods have become general tools for engineering proteins. However, almost all these methods depend on the translation elongation process, and strategies leveraging the initiation process have rarely been reported. The incorporation of a ncAA specifically at the translation initiation site enables the installation of reactive groups for modification at the N-termini of proteins, which are attractive positions for introducing abiological groups with minimal structural perturbations. In this study, we attempted to engineer an orthogonal protein translation initiation system. Introduction of the identity elements of Escherichia coli initiator tRNA converted an engineered Methanococcus jannaschii tRNATyr into an initiator tRNA. The engineered tRNA enabled the site-specific incorporation of O-propargyl-l-tyrosine (OpgY) into the amber (TAG) codon at the translation initiation position but was inactive toward the elongational TAG codon. Misincorporation of Gln was detected, and the engineered system was demonstrated only with OpgY. We expect further engineering of the initiator tRNA for improved activity and specificity to generate an orthogonal translation initiation system.